Spinoza's heresy : immortality and the Jewish mind - Nadler, Steven M., 1958- (Clarendon ; Oxford University Press, 2004)
At the heart of Spinoza's Heresy is a mystery: why was Baruch Spinoza so harshly excommunicated from the Amsterdam Jewish community at the age of twenty-four? In this philosophical sequel to his acclaimed, award-winning biography of the seventeenth-century thinker, Steven Nadler argues that Spinoza's main offence was a denial of the immortality of the soul. But this only deepens the mystery. For there is no specific Jewish dogma regarding immortality: there is nothing that a Jew is required to believe about the soul and the afterlife. It was, however, for various religious, historical and political reasons, simply the wrong issue to pick on in Amsterdam in the 1650s. After considering the nature of the ban, or cherem, as a disciplinary tool in the Sephardic community, and a number of possible explanations for Spinoza's ban, Nadler turns to the variety of traditions in Jewish religious thought on the postmortem fate of a person's soul. This is followed by an examination of Spinoza's own views on the eternity of the mind and the role that that the denial of personal immortality plays in his overall philosophical project. Nadler argues that Spinoza's beliefs were not only an outgrowth of his own metaphysical principles, but also a culmination of an intellectualist trend in Jewish rationalism.